Vulvo-perineal and perianal Paget disease. Radical excision and reconstruction with Singapore flap - Panoskaltsis, Theodoros; Arkoumanis, Theofanis Panagiotis; Panagopoulos, Nikolaos; Mastorakos, Dimitrios (Acta Medica, 2019)
Extramammary Paget disease (EMPD) is an uncommon intraepithelial malignancy, affecting the vulvo-perineal and perianal region, occurring in 6.5% of all Paget diseases. Usually, an underlying invasive adenocarcinoma denotes a more aggressive behaviour of the disease. We present the multidisciplinary approach in a 75-year old patient with this rare disease. The patient underwent a radical surgical excision and, subsequently, a Singapore flap was used for primary closure. The final histology confirmed the presence of a non-invasive Paget tumor, but a focus of high-grade invasive adenocarcinoma was noted in a perineal nodule. The histological margins were free of tumor. The patient did not undergo any adjuvant treatment because of severe chronic medical problems, although, eighteen months after treatment, she remains well, with no signs of recurrence. In conclusion, radical surgical excision, often necessitating reconstruction techniques, remains the gold standard of care and further adjuvant treatment should be individualised.
Keywords: adjuvantní radioterapie; Aged; Treatment Outcome; senioři; Radiotherapy, Adjuvant; lidé; nádory vulvy; Anus Neoplasms; lokální recidiva nádoru; Plastic Surgery Procedures; Neoplasm Recurrence, Local; Female; Vulvar Neoplasms; výsledek terapie; Free Tissue Flaps; ženské pohlaví; Humans; zákroky plastické chirurgie; volné tkáňové laloky; nádory anu; Paget Disease, Extramammary; extramamární Pagetova nemoc